2013
DOI: 10.1073/pnas.1320659110
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible copy number variation patterns among single circulating tumor cells of lung cancer patients

Abstract: Circulating tumor cells (CTCs) enter peripheral blood from primary tumors and seed metastases. The genome sequencing of CTCs could offer noninvasive prognosis or even diagnosis, but has been hampered by low single-cell genome coverage of scarce CTCs. Here, we report the use of the recently developed multiple annealing and looping-based amplification cycles for whole-genome amplification of single CTCs from lung cancer patients. We observed characteristic cancer-associated single-nucleotide variations and inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
364
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(375 citation statements)
references
References 43 publications
8
364
1
Order By: Relevance
“…Direct molecular characterization of CTCs requires further purification beyond current enrichment strategies, which retain a considerable amount of leukocytes (11). For example, CTC enriched samples obtained via modified versions of the CellSearch method have been subjected to molecular profiling (28)(29)(30)(31). In addition, some methods may provide relative advantage in terms of ability to isolate CTCs usable for genomic and expression analysis (11).…”
mentioning
confidence: 99%
“…Direct molecular characterization of CTCs requires further purification beyond current enrichment strategies, which retain a considerable amount of leukocytes (11). For example, CTC enriched samples obtained via modified versions of the CellSearch method have been subjected to molecular profiling (28)(29)(30)(31). In addition, some methods may provide relative advantage in terms of ability to isolate CTCs usable for genomic and expression analysis (11).…”
mentioning
confidence: 99%
“…150 The study researchers also found that a small number of individuals with lung adenocarcinoma (N = 4) exhibited nearly identical global CNV patterns (78% of the gain and loss regions were shared). 150 This finding could suggest the possibility that CTC CNV analysis may be a biomarker for lung adenocarcinoma. It is likely that the genetic analysis of CTCs will be an important area in the development of biomarkers for cancer.…”
Section: Molecular Characterizationmentioning
confidence: 67%
“…Because CTCs are a heterogeneous population of cells, single-cell genetic analysis will be required, as will searching the profile(s), determining the metastatic potential of the tumor cell, and understanding the copy number variations of specific genes known to be critical in CTCs. In their study of lung cancer, Ni et al 150 illustrated that all CTCs from a given individual, irrespective of cancer subtype, showed reproducible copy number variation patterns similar to the metastatic tumor in the same individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell sequencing helped to discover clonal mutations, cryptic cell types, or transcriptional features that would be diluted or averaged out in bulk tissue. [85][86][87] To provide the proof of concept, genome-wide SNPs and CNVs were successfully detected by using a single human cell. 88 Using single-cell sequencing, McConnell et al further showed that mosaic CNV is abundant in human neurons.…”
Section: Future Directionsmentioning
confidence: 99%